Empowering Female Farmers Against Mining Capitalism - Huda, Miftahul; Chusna, Alfa (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2020)
Women mostly depend on agriculture, which indicates that women have their economic resources to help the family economy. The presence of the Kulon Progo Coastal Farmers Association of Farmers is the beginning of a bright future for farmers, women. This article discusses the empowerment of women in the Kulon Progo Coast Farmers Association. The purpose of this study is to find out how far women can be empowered with the organization of the Kulon Progo Coastal Farmers Association. This research is a qualitative study with data collection techniques using a purposive sample. The data collection process is done by in-depth interviews and snowball after the key informant is found. The data obtained were analyzed using the Longwe analysis framework. The results of this study indicate that female farmers are equal in agricultural areas, but in the political domain (organization) female farmers are still below male farmers.